1973
DOI: 10.1073/pnas.70.12.3478
|View full text |Cite
|
Sign up to set email alerts
|

Early Differentiation of Glucagon-Producing Cells in Embryonic Pancreas: A Possible Developmental Role for Glucagon

Abstract: Glucagon and insulin are first detectable at the onset of rat pancreas organogenesis. Initially, the specific activity of glucagon is approximately 100-fold higher than that of insulin. At this early stage, endocrine storage granules, similar to a granules, are identifiable in electron micrographs. The granule characteristics, as well as the relative hormone levels, suggest that the early population of differentiated endocrine cells is in fact composed of glucagon-producing (A) cells. This high level of glucag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
45
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 22 publications
3
45
0
Order By: Relevance
“…Prior to the grafting of these pancreases, we characterised the presence of endocrine and exocrine tissue in the explant by immunofluorescence analysis. In accordance with previously reported results [34], at E16.5 the vast majority of the endocrine cells in the pancreas are glucagon-expressing cells, in addition to rare insulin-expressing cells (Fig. 2a).…”
Section: Resultssupporting
confidence: 93%
“…Prior to the grafting of these pancreases, we characterised the presence of endocrine and exocrine tissue in the explant by immunofluorescence analysis. In accordance with previously reported results [34], at E16.5 the vast majority of the endocrine cells in the pancreas are glucagon-expressing cells, in addition to rare insulin-expressing cells (Fig. 2a).…”
Section: Resultssupporting
confidence: 93%
“…During the next 3-4 d, acinar structures form and the low levels of exocrine secretory proteins and insulin are maintained ("protodifferentiated state") (22, 23) . A second differentiative transition is detectable beginning at 14-15 d gestation when there is a rapid increase in rough endoplasmic reticulum, a 103-to 10'-fold increase in the accumulation of the specific exocrine enzymes and insulin, coupled with the appearance of zymogen granules in acinar cells and,8 granules in B cells (4,21,23) accumulate in a parallel fashion but slightly preceding the secretory proteins (10,11,20) .…”
mentioning
confidence: 99%
“…Normal development requires interaction between epithelial and mesenchymal tissues (8,25). Early investigations suggested that pancreatic differentiation is a multiphasic process (4,21,23) . In the rat, the formation of the pancreatic rudiment from the gut at -11 d gestation is coupled to the appearance of very low levels of exocrine proteins and insulin (the primary transition) .…”
mentioning
confidence: 99%
“…Somatostatin inhibits the release of insulin and glucagon from B and A cells, respectively, in the pancreatic islet both in vivo and in vitro [1,7,8,10,11]. Early development of somatostatin cells has not been much studied in detail, although that of A and B cells has been widely investigated in the rat fetus [5,6,[16][17][18]. The present study was performed to determine when somatostatin cells would appear and in what fashion they would grow in the rat fetus, by means of the immunocytochemical technique.…”
mentioning
confidence: 97%
“…It is proposed that B cells of the fetal pancreas differentiate by 3 steps [9,13]. In the first step up to day 15, B cells reveal no signs of cytological differentiation with constantly low insulin content and with undetectable insulin granules by ultrastructural analysis [16,17]. In the second step around day 15, B cells reveal a cytodifferentiation characterized by the appearance of secretory granules and an exponential increase in the cell volume and the insulin content [12].…”
mentioning
confidence: 99%